Researching participatory arts, well-being and health: Some methodological issues. (4th May 2012) - Skingley, Ann; Bungay, Hilary; Clift, Stephen
This article considers some of the methodological issues faced by a team working in the emerging field of participatory arts and health research. It argues that, in order to optimize research rigour, there is a need to address four fundamental issues. First, researchers should define the scope of the art(s) under study (in terms of domain, level of participation and potential impact); second, they should adopt a concept of health appropriate for the target sample group; third, the research method should be consistent with the extent and type of evidence already existing in the area and that to be sought; and finally, there is a need to select a means of data collection and communication that accurately represents both the outcomes/impacts of arts interventions and the experiences of research subjects, which may not be reducible to the language conventionally used in research. The issues are illustrated with an account of one research project being undertaken by the team.